Analisis Sistem Informasi Rehabilitasi Narkoba dengan Metode HOT FIT pada Klinik BNN Guna Menunjang Ketahanan Nasional - Fauzia, Atina; Sri Rahayu, Amy Yayuk; Harahap, Anggi Aulina (Jurnal Kajian Stratejik Ketahanan Nasional, 2021)
The Narcotics Rehabilitation Information System (SIRENA) belonging to the National Narcotics Agency (BNN) managed by the Deputy for Rehabilitation provides narcotics rehabilitation data needed to support decision making. Given the important role of SIRENA BNN, analysis is needed to identify and evaluate existing problems and potential future developments. This study aims to analyze in order to gain an understanding and to study more deeply the BNN SIRENA using the HOT FIT method in terms of human, organizational, technological, and net benefits components. This study uses a descriptive analytical qualitative approach with data collection techniques through in-depth interviews, observation and documentation. The informants in this study were 10 (ten) people who were users of the BNN SIRENA benefits, namely the BNN Rehabilitation Deputy, Rehabilitation Person in Charge and Operator at the BNN IPWL Clinic in the DKI Jakarta area. The results showed that from the human component, the frequency of use was adjusted to data needs, there was good training and knowledge for users, there was hope for future development, good acceptance, good perception and satisfaction from users. Keywords: Analysis; Information Systems; Narcotics; HOT FIT Method